Sex differences in elite track and field performances and inferences about steroid doping - Collantes, D. B.; Senefeld, J. W.; Larson, K. F.; Coleman, D. L.; Joyner, M. J.; Kipp, S. (Experimental Physiology, 2025)
Females likely experience larger performance benefits from androgenic-anabolic steroids than males. We set out to determine if there were temporal differences in select athletics (track and field) records between females and males. Exploratory aims included: (1) evaluating the improvements in female and male world records over time, and (2) investigating the influence of doping programs on male and female world records before and after 1990, when sports governing bodies began to implement random out-of-competition and systematic in-competition drug testing. We collected the top 500 performances of all time for both sexes from an online database (worldathletics.org) in four running events (100, 200, 400 and 800 m) and two throwing events (discus throw and shot-put). Data were stratified into quintiles based on world record ranking (1st to 100th, 101st to 200th, etc.). The temporal distribution of the top 100 female performers was significantly earlier than the top 100 male performers (year: 2000 ± 1 vs. 2005 ± 1, respectively; P < 0.0001). Within the event, the top performances occurred significantly earlier for females in the 800 m (year: 1995 ± 15 vs. 2003 ± 12; P = 0.0007) and shot-put (year: 1992 ± 14 vs. 2003 ± 17; P = 0.0004). Among females, world records rapidly improved through the 1980s, but following 1990, the world records ceased to improve. Geographically, there was a greater representation of countries with state-sponsored doping programs, specifically among female performances. We postulate these sex differences in the temporal distribution of top performances are likely associated with enhanced effectiveness of exogenous androgens (steroid doping) among female athletes with lower endogenous androgen hormones compared to males.